PEMBERDAYAAN GURU MELALUI KETRAMPILAN KREATIF UNTUK MENGEMBANGKAN PENGETAHUAN DAN BAKAT ANAK PENYANDANG DISABILITAS DI MI AL MA’ARIF 2 JOMBANG JEMBER - Khurin In Ratnasari; Dukan Jauhari F (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
Empowering children with disabilities through creative skills development is important in supporting their learning process. In MI Al Ma’arif 2 Jombang Jember, children with disabilities are often limited in accessing various opportunities to develop their potential. Therefore, this empowerment aims to develop the knowledge and talents of children with disabilities through creative skills, with the hope of improving their cognitive, social, and emotional abilities. The method used in this service is ABCD with the technique Define (Determine) Discovery (Deep Discovery), Dream (Dream). Design. Deliver or Destiny (Implement and Control or Evaluate). This service involves teachers in supporting the development of children's creative skills. The results showed that creative skills activities, such as drawing, hand art, and music, can improve self-confidence, social skills, and problem-solving ability. Teachers who participated in the programme showed significant improvement in their ability to master learning methods in the inclusive classroom and had better interaction skills Overall, empowerment through creative skills contributed positively to the development of knowledge and talents of children with disabilities in MI Al Ma’arif 2 Jombang Jember.